Annexin A2 Enhances the Progression of Colorectal Cancer and Hepatocarcinoma via Cytoskeleton Structural Rearrangements. (August 2019) - He, Huimin; Xiao, Li; Cheng, Sinan; Yang, Qian; Li, Jinmei; Hou, Yifan; Song, Fengying; Su, Xiaorong; Jin, Huijuan; Liu, Zheng; Dong, Jing; Zuo, Ruiye; et al.
Abstract: Annexin A2 (ANXA2) is reported to be associated with cancer development. To investigate the roles ANXA2 plays during the development of cancer, the RNAi method was used to inhibit the ANXA2 expression in caco2 (human colorectal cancer cell line) and SMMC7721 (human hepatocarcinoma cell line) cells. The results showed that when the expression of ANXA2 was efficiently inhibited, the growth and motility of both cell lines were significantly decreased, and the development of the motility relevant microstructures, such as pseudopodia, filopodia, and the polymerization of microfilaments and microtubules were obviously inhibited. The cancer cell apoptosis was enhanced without obvious significance. The possible regulating pathway in the process was also predicted and discussed. Our results suggested that ANXA2 plays important roles in maintaining the malignancy of colorectal and hepatic cancer by enhancing the cell proliferation, motility, and development of the motility associated microstructures of cancer cells based on a possible complicated signal pathway.